The Media and Criminal Policy: A Conflictive Relationship - Borges Terra, Luiza (2022)
This article develops some aspects of freedom of the press and how its abuse can affect criminal policy in different ways. It explains how criminal policy is affected in three ways: the distortion of information and the use of rhetoric; the propagation of the idea that criminal law is the solu-tion; and the direct influence on the public agenda.